Impact of Electronic Banking on Customer Satisfaction in Nepalese Commercial Banks - Adhikari, Nabin Bahadur (Kalika Journal of Multidisciplinary Studies, 2024)
E-banking is one of the fastest adopted tools even by Nepalese customers. Due to its different features, it became most popular tool in Nepal in a very short time reaching numbers of customer meeting their needs. . Customer satisfaction can be effected by number of items. The focus of this study is to examine the relationship and impact of electronic banking on the customer satisfaction in Nepalese commercial banks. The basis of this study is primary sources of data, which are collected through questionnaire. An online questionnaire survey was conducted to gather the data and 112 complete responses were gathered from Universities/Colleges located in Pokhara valley. The descriptive and causal research design was used. The collected data were analyzed and interpreted with the help of different statistical tools and IBM SPSS software. The descriptive and inferential statistical was used. The independent variable was considered as convenience, cost, privacy, security and responsiveness and the customer satisfaction is considered as dependent variable. The result emphasizes that there is positive and significant relationship between the variables. In addition, it is argued that no significant relation between customer satisfactions to ‘privacy’. Moreover, all the dependent and independent variables found to have positive relation to each other. As a result, the research recommends that customer satisfaction on e-banking system is statistically significant with convenience, responsiveness, cost and security but not with privacy.